Kinetic of Adsorption Process of Sulfonated Carbon-derived from Eichhornia crassipes in the Adsorption of Methylene Blue Dye from Aqueous Solution - Mukhamad Nurhadi; Iis Intan Widiyowati; Wirhanuddin Wirhanuddin; Sheela Chandren (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
The evaluation of kinetic adsorption process of sulfonated carbon-derived from Eichhornia crassipes in the adsorption of methylene blue dye from aqueous solution has been carried out. The sulfonated carbon-derived from E. crassipes (EGS-600) was prepared by carbonation of E. crassipes powder at 600 °C for 1 h, followed by sulfonation with concentrated sulfuric acid for 3 h. The physical properties of the adsorbents were characterized by using Fourier transform infrared spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), and nitrogen adsorption-desorption studies. Adsorption study using methylene blue dye was carried out by varying the contact time and initial dye concentration for investigated kinetics adsorption models. The effect of varying temperature was used to determine the thermodynamic parameter value of ΔG, ΔH, and ΔS. The results showed that the equilibrium adsorption capacity was 98% when EGS-600 is used as an adsorbent. The methylene blue dye adsorption onto adsorbent takes place spontaneity and follows a pseudo-second-order adsorption kinetic model.